PENGETAHUAN CEDERA OLAHRAGA PADA MAHASISWA FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PEKAJANGAN PEKALONGAN - Dias Arif Budiani, Dias arif budiani (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2024)
Every sports actor has a risk of experiencing injury when doing physical activities such as physical education, achievement sports and fitness sports. Every UMPP graduate and student is expected to have the ability to be able to prevent and deal with injuries that occur. The purpose of this study was to determine the level of sports injury knowledge of UMPP students related to various types of sports injuries, injury locations, factors that cause sports injuries, treatment of sports injuries and efforts to prevent sports injuries. The research method uses survey techniques by distributing questionnaires and interviews given to UMPP students. The population and sample of this study were fourth semester UMPP students in the 2015/2016 school year, taking samples using random sampling. The results of this study were that the level of knowledge of sports injuries in Semester 2 students was 26% in the very high category, 72% in the high category and 2% in the moderate category. The level of knowledge of injuries in semester 6 students is 4% in the very high category, 86% in the high category, and 10% in the moderate category; The level of knowledge of semester 4 students is 92% in the high category and 8% in the medium category. UMPP students have not been able to implement sports injury management. The conclusion of this study is that the level of sports injury knowledge of UMPP students is in the high category